Lynn Jones (ed.). Byzantine Images and their Afterlives. Essays in Honor of Annemarie Weyl Carr - Cormack, Robin (Journal of Greek Archaeology, 2018)
This festschrift to mark the retirement of Professor Annemarie Weyl Carr as a teacher at the Southern Methodist University at Dallas, Texas, has three distinctive features. One is the extraordinarily effusive tributes to her by the contributors. The second is the high quality of the twelve papers. The third is the full and dense documentation of these papers – there is no waffle.